2011
DOI: 10.1111/j.1600-0609.2011.01640.x
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity for patients undergoing an allogeneic hematopoietic stem cell transplantation: benefits of a moderate exercise intervention

Abstract: The results show that the training program is feasible and seems to have positive influences on physical performance and quality of life in patients undergoing an allogeneic HSCT. However, further studies are necessary to confirm these results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
140
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 113 publications
(149 citation statements)
references
References 33 publications
5
140
0
4
Order By: Relevance
“…Only a small non-significant increase ( þ 10%) in one measured muscle group (hip-flexor) was seen in the unfit group. Comparable results were reported by others 10,25 showing that exercising under allo-HCT can prevent the loss of physical performance, but does not result in increases. Furthermore, the study by Defor et al 26 also showed comparable results with regard to the Karnofsky performance score.…”
Section: Discussionsupporting
confidence: 71%
“…Only a small non-significant increase ( þ 10%) in one measured muscle group (hip-flexor) was seen in the unfit group. Comparable results were reported by others 10,25 showing that exercising under allo-HCT can prevent the loss of physical performance, but does not result in increases. Furthermore, the study by Defor et al 26 also showed comparable results with regard to the Karnofsky performance score.…”
Section: Discussionsupporting
confidence: 71%
“…Thus, data extraction was performed on 18 papers. Two of the papers were publications based on the same study and were excluded [27,28], leaving 16 trials for final synthesis. Figure 1 shows the outcome of the search process and selection of studies.…”
Section: Search Results and Selection Of Studiesmentioning
confidence: 99%
“…The onset timing of physical exercise intervention for allo-HSCT patients varies, and can occur in 1 of 3 phases: conditioning (before HSCT) [11][12][13][14][15][16][17], post engraftment (after HSCT) [18,19], or hospital discharge phase [20][21][22][23][24]. Recently, physical exercise intervention has reportedly been increasingly initiated during the conditioning phase (chemotherapy and radiation therapy regimen).…”
Section: Physical Exercise Intervention Periodmentioning
confidence: 99%
“…Physical exercise intervention is usually fully [11,[13][14][15][16][17][18][19][20][21] or partially supervised [12] in patients undergoing allo-HSCT. Interestingly, Shelton et al [22] reported higher endurance and gait speeds in supervised training groups than that in patient-directed training groups.…”
Section: Types Of Exercise Interventionmentioning
confidence: 99%
See 1 more Smart Citation